Antidepressant Mechanism of Traditional Chinese Medicine Formula Xiaoyaosan in CUMS-Induced Depressed Mouse Model via RIPK1-RIPK3-MLKL Mediated Necroptosis Based on Network Pharmacology Analysis - Yan, Zhi-Yi; Jiao, Hai-Yan; Chen, Jian-Bei; Zhang, Kai-Wen; Wang, Xi-Hong; Jiang, You-Ming; Liu, Yue-Yun; Xue, Zhe; Ma, Qing-Yu; Li, Xiao-Juan; Chen, Jia-Xu (Frontiers in Pharmacology, 2021)
Objective: To investigate the efficacy of Xiaoyaosan in mice with depression using network pharmacology method, and identify the potential targets of necroptosis underlying the antidepressant mechanism of Xiaoyaosan. Methods: The mice model of depression was induced by CUMS for 6 weeks. Adult C57BL/6 mice were randomly divided into 5 groups, including control group, CUMS group, Xiaoyaosan treatment group, Nec-1 group and solvent group. Drug intervention performed from 4th to 6th week of modeling. The mice in Xiaoyaosan treatment group received Xiaoyaosan by intragastric administration (0.254 g/kg/d), and mice in CUMS group received 0.5 mL physiological saline. Meanwhile, the mice in Nec-1 group were injected intraperitoneally (i.p.) with Nec-1 (10 mg/kg/d), and the equivalent volume of DMSO/PBS (8.3%) was injected into solvent group mice. The behavior tests were measured to evaluate depressive-like behaviors of model mice. Then, the active ingredients in Xiaoyaosan and the related targets of depression and necroptosis were compiled through appropriate databases, while the “herbs-active ingredients-target genes” network was constructed by network pharmacology analysis. The expressions of RIPK1, RIPK3, MLKL, p-MLKL were detected as critical target genes to verify the exist of necroptosis and the potential therapeutic target compounds of Xiaoyaosan. Furthermore, the levels of neuroinflammation and microglial activation of hippocampus were measured by detecting the expressions of IL-1β, Lipocalin-2 and IBA1, and the H&E stained was used to observe the morphology in hippocampus sections. Results: After 6-week of modeling, the behavioral data showed that mice in CUMS group and solvent group had obvious depressive-like behaviors, and the medication of Xiaoyaosan or Nec-1 could improve these behavioral changes. A total of 96 active ingredients in Xiaoyaosan which could regulate the 23 key target genes were selected from databases. Xiaoyaosan could alleviate the core target genes in necroptosis and improve the hippocampal function and neuroinflammation in depressed mice. Conclusion: The activation of necroptosis existed in the hippocampus of CUMS-induced mice, which was closely related to the pathogenesis of depression. The antidepressant mechanism of Xiaoyaosan included the regulation of multiple targets in necroptosis. It also suggested that necroptosis could be a new potential target for the treatment of depression.